Al-Zarnuji’s Character Concept in Strengthening Character Education in Indonesia - Djeprin E. Hulawa (Jurnal Pendidikan Islam, 2018)
This study aims to find the relevance and contextualization of the thoughts of al-Zarnuji's character in the present context especially in relation to strengthening character education in Indonesia. The research used the incorporative approach and descriptive, heuristic and hermeneutic methods. The analysis technique used analytical content. The study found that there was relevance in the concept of al-Zarnuji's character to the concept of strengthening character education in Indonesia, where both of them made aspects of noble character and morality as the pillars and main souls of humans in nation-building. Although in a different socio-cultural context, the concept of al-Zarnuji's character and the concept of character education in Indonesia both go in the same direction, namely the effort to establish positive characters for students through education.